Development of Teaching Materials for Al-arabiyah Sabiluna to Improve Speaking Skills of Grade 2 Students of Alwildan 4 International Islamic School Jakarta - Ibrahim, Anri (Rayah Al-Islam, 2025)
Objectives of this research: (1) Revealing the needs of the textbook. (2) Revealing the steps to develop the Arabic book as a way to promote the speech skill of the second grade students in the fourth boy's school. (3) The effectiveness of the Arabic book is our way to promote the speech skill of the second grade students in the fourth Waldan school. This research is a developmental research from the Borg and Gall model. The research subject is second grade students. The results of the research indicate that: (1) After the researcher met with Arabic language teachers and the head of the school that students do not speak Arabic about daily expressions. (2) The researcher used the Borg and Gall development model in developing the material for this book. (3) The researcher shows the difference between the mean of the pre-test and the post-test, the mean of the pre-test is 17.5 and the post-test is 57.2, so the difference between them is about 39.7. It shows the relationship between the pre-test and post-test, and the table shows that the result of the experimental section is 48.12 and the result of the non-experimental section is 42.99, meaning that there is a relationship between the pre-test and the post-test, as the result of the experimental section is higher than the result of the non-experimental section about 5.14, so we conclude that this book is effective in promoting the skill of speech in learning the Arabic language, so we conclude that this advanced book Arabic Sabeelna is effective.